Evaluation of Glycogen Phosphorylase BB (GPBB) Level in Serum as Marker in Diagnosis of Acute Ischemic Stroke - Gheyath AlGawwam; Zeena abdul Iilah; Maryam Emad Shake (Institute of Medico-legal Publications Pvt Ltd, 2021)
Objective: We aimed to investigate whether Serum levels of glycogen phosphorylase BB (GPBB) isoformcould be used as a potential diagnostic biomarker in Acute Ischemic Stroke (AIS) patients or not.Materials and methods : glycogen phosphorylase BB were prospectively evaluated in 40 patients agedbetween 40 to 70 y who were admitted within 24 h of the onset of AIS. The control group included 40healthy volunteers of similar age without any disease.Results: There is a significant elevation in the level of GPBB in ischemic stroke group and compared withcontrol group. For Control, the observations of GPBB had an Min = 4.91 For Stroke, the observations ofGPBB had an Min = 15.32There was a significant positive correlation between stoke and Glycogen phosphorylase (rpb = 0.7473,p< .001). The correlation coefficient between Stroke and Glycogen phosphorylase was 0.7473 indicatinga large effect size. This indicates that moving from the Not having to having Stroke is associated withan increase in Glycogen phosphorylase. Therefore, Stroke tends to be associated with higher values ofGlycogen phosphorylaseConclusions: 1-This study shows there is significant elevation in enzyme level of glycogen phosphorylaseBB (GPBB) in ischemic stroke group and compared with control group.